Configuration institutionnelle nationale et gouvernance locale des biens communs complexes - Nona Nenovska (Revue de la Régulation)
This article focuses on the study of complex commons in the context of institutional and socio-economic dynamics in Bulgaria. The work focuses on highlighting the institutional arrangements produced by different actors at local level that underpin the governance of the Kaliakra marine protected area (MPA) and the harvesting of the invasive species Rapana venosa. The socio-ecological systems framework, developed by Elinor Ostrom, is used to analyse the effectiveness of governance, focusing on the collective action of stakeholders within a ’weak state’. The conclusions highlight the importance of path dependency and the participation of all stakeholders in the governance process, particularly local residents. The type of local governance (the institutional arrangement) that is formed may take a different path from that prescribed by formal institutions. This can be explained by the path dependency that comes up against pre-existing institutional configurations.